ZUR FÖRDERUNG DER SPRACHBEWUSSTHEIT – VERGLEICHEN UND BESPRECHEN DER GRAMMATISCHEN STRUKTUREN - Hinc, Jolanta (Neofilolog, 2019)
This paper elaborates on the notion of language awareness among multilingual students. In the first part the author presents the results of a research study whose objective was to assess if multilingual students are aware that the languages they speak and study (English and German) interact constantly and if they recognize the phenomenon of the positive and negative transfer. The subjects were students of Applied Linguistics at the universities of Bydgoszcz, Gdańsk and Poznań in Poland. The second part of the article is an attempt to connect theory and practice. It contains some suggestions how to improve multilingual foreign language teaching. A comparison and discussion of grammar structures aims to promote language awareness among students of foreign languages.